Pharmacokinetics and bioavailability of calcium fosfomycin in post weaning piglets after oral administration - Pérez, Denisa Soledad (2012)
Calcium fosfomycin pharmacokinetics and bioavailability were studied in post weaning piglets after oral administration at 30 mg/kg of bodyweight (BW)). Fosfomycin plasma concentrations were measured by high-performance liquid chromatography MS/MS. The T1/2 was of 1.80 ± 0.89 h. Cmax, Tmax and bioavailability were 3.60 ± 0.96 µg/mL, 3.00 ± 0.00 h and 20.0 ± 1.85 %, respectively. The area under the fosfomycin concentration:time curve in plasma AUC(0-∞) was 45.48 ± 9.20 µg h/mL. Different authors have determined a minimum inhibitory concentration ranging from 0.25 - 0.5 µg/mL for Streptococcus sp. and Escherichia coli, respectively. Considering these minimum inhibitory concentrations of sensitive bacteria to fosfomycin, taking into account fosfomycin is a time-dependent antimicrobial and according to the values of fosfomycin plasma concentration vs. time profiles observed in this study, it was determined that effective plasma concentrations of fosfomycin for sensitive bacteria can be obtained following oral administration of fosfomycin at a dose of 30 mg/kg in piglets.